The Mystery of Misuse of School Operational Assistance Funds: An in Depth Analysis Using The Fraud Hexagon (Pusat Riset dan Inovasi Nasional, 2025)
This study aims to examine patterns of misuse of School Operational Assistance (BOS) funds across 14 regencies/municipalities in West Papua and Southwest Papua Provinces during the 2022–2024 period. BOS funds constitute a strategic public financing instrument designed to support the operational needs of primary and secondary education; however, their implementation remains vulnerable to governance failures and fraud. The primary research problem addressed is the persistence of weak accountability and internal control mechanisms that enable systemic misuse of education funds. This study employs a qualitative approach using directed content analysis of 42 Audit Reports (LHP) issued by the Audit Board of Indonesia (BPK) on Local Government Financial Statements (LKPD), triangulated with data from the Corruption Eradication Commission’s (KPK) Education Integrity Assessment Survey (SPI) and relevant legal documents. The analysis is guided by the Fraud Hexagon framework, which encompasses pressure, opportunity, rationalization, capability, arrogance, and collusion. The findings reveal that opportunity, arising from deficiencies in internal control systems and regulatory compliance, is the most dominant fraud dimension across all regions and years. The study concludes that BOS fund misuse is systemic in nature and underscores the need for strengthened governance structures.